Innovation potential teachers of vocational schools and colleges: essence, development factors and reasons interdisciplinary research - Valentin Klyshkin; Alexandr Mischenko; Alexei Fedorov (International Society of Philosophy and Cosmology, 2014)
The The essence and structure of modern innovation potential teachers. The use of sociological tools, factors disclosed development and innovation base of interdisciplinary research potential of teachers.